Sound Absorption Properties of Sound Absorption Materials Using Zelkova serrata Leaves - 배은지; 고준호; 염다혜; Kyung-Rok Won; 공이근; 변희섭(College of Agriculture & Life Science, Gyeongsang National University; Institute of Agriculture & Life Science, Gyeongsang National University) (Journal of Forest and Environmental Science, 2024)
This study analyzes the characteristics of sound-absorbing materials made from forest by-products of the deciduous tree species Zelkova serrata (Z. serrata) by evaluating their sound absorption performance. Accordingly, sound-absorbing materials with varying sample thicknesses, leaf sizes, and drying conditions were fabricated. The sound absorption properties were measured using the impedance tube method via middle-type measurement tube (100 Hz-3,200 Hz). The sound absorption properties were evaluated using the average sound absorption coefficient (ASAC), which was calculated from the measured sound absorption coefficients at 250 Hz, 500 Hz, 1,000 Hz, and 2,000 Hz. The ASAC value significantly improved as the leaf size increased to 0.5×0.5 cm2, 1.0×1.0 cm2, and 2.0×2.0 cm2. The ASAC values under the two drying conditions were similar. There was no significant difference in ASAC according to the leaf size under the air-dried leaf condition, with a thickness of 2.50 cm. The highest ASAC value according to the sound-absorbing material thickness was 0.47 at a thickness of 2.50 cm and leaf size of 2.0×2.0 cm2 under the air-dried leaf condition. In addition, the variation in ASAC was 0.23, indicating that the sound absorption performance according to leaf thickness was more significant than the difference in absorption properties according to leaf size. A sound absorption coefficient (SAC) of 0.4 or higher was observed across the measurable frequency band (100 Hz-3,200 Hz). Furthermore, the SAC values with respect to leaf size and thickness were close to 1 in the high-frequency range above 2,000 Hz. Therefore, it is considered that sound-absorbing materials using Z. serrata leaves are advantageous in the field of absorbing noise in a high-frequency band of 2,000 Hz or more, and it is better to manufacture a thickness of 2.50 and 2.0×2.0 cm2.